Enhancing Problem-Solving Skills on Ethnic Diversity Through Problem-Based Learning in Fifth-Grade Students - Handoyo, Wiryo Sastro; Safran, Safran (Journal of Social Work and Science Education, 2025)
This study aims to examine the application of Problem-Based Learning (PBL) strategies in improving students’ problem-solving skills on the topic of ethnic diversity in fifth grade at MIS Hidayatussalam. PBL was chosen as a learning approach to encourage students not only to understand the material theoretically, but also to think critically and develop problem-solving skills relevant to social issues in everyday life. The method used in this study is a qualitative method with a descriptive approach, which involves participatory observation and interviews with teachers and students. The results of the study indicate that the successful implementation of PBL improves students’ critical thinking skills and their ability to analyze and solve social problems related to ethnic diversity. Students become more active in class discussions, more confident in expressing opinions, and better able to connect learning materials with social issues that occur in society. Despite challenges, such as low initial student participation and difficulties in connecting the material to real life, the implementation of PBL has proven effective in improving students’ problem-solving skills. This study recommends that PBL can be an alternative effective learning strategy to develop students’ critical thinking and problem-solving skills in schools.